+0  
 
0
135
1
avatar

hi. how do i solve this x^2 – 6x + 5 ≥ 0

Guest Mar 5, 2017
 #1
avatar+87301 
+5

x^2 - 6x + 5 ≥ 0 

 

Set this to 0

 

x^2 - 6x + 5  = 0       factor

 

(x - 5) ( x - 1)  = 0   set each factor to  0   and solve  and x = 5 and x =1

 

The solution to the original inequality will come from either of these two intervals (-inf,1] and [5, inf) or from the interval  [1, 5]

 

Note that testing any point between x = 1 and x = 5 will make the inequality false

 

So.....the solution is   x = (-inf, 1] U [5, inf )

 

 

cool cool cool

CPhill  Mar 5, 2017

14 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.